Epidemiology of 258 Surgically Treated Cases of Lumbar Disc Prolapse. (May 2014) - Zahoor, A.; Jayachandran, R. Kumar; Ashraf, S.; Unnikrishnan, R.; Menon, K. V.
Introduction: Low back pain (LBP) is common with a lifetime prevalence of 70% and sciatic conditions in one quarter. Most of the research related to spine surgery is focused on the methods and techniques of diagnosis, therapy and rehabilitation, but hardly anything has been published on disease prevention and avoiding the need for surgery. The purpose of this study is to examine the epidemiological characters and investigate risk factors that predispose individuals to LIVDP. Materials and Methods: This is an observational, noninterventional, descriptive study of 500 surgically treated cases of lumbar disc prolapse in a tertiary spine care center over 7 years' time. Data were collected through questionnaires, outpatient registers, X-rays, MRI scans, and operation notes. Variables studied were age, body mass index, occupation, intensity of physical labor at work, driving, smoking, level of education, socioeconomic status, recreational activities, and family history of LIVDP. Data were analyzed and depicted in the form of various charts, tables, graphs, and histograms according to their occurrence. Results: In our study, 26 to 45 years is the most common age group affected with LIVDP. Males were 69.8% with progressive increase in the difference as the age increases; 54.65% patients hailed from rural population, 70.54% occupations were involved in sedentary type of work with excessive bending and twisting activities, and only 28.68% were from the heavy manual group involved in lifting and other strenuous activities. Driving was a significant factor 60.47% with dominance of two wheeler drivers by 58.97%. Trauma was an event initiating back pain in 34%. Family history of back pain or spine surgeries was not significant. There was no effect of smoking or drinking. Total 84.5% were having sedentary habits with no sporting activities. Anxiety and stress were found in 61.7% people with 38.8% having it before the surgery. Conclusion: Most common age group presenting with lumbar disc prolapse is 26 to 45 years with two-thirds predominance of males. Light manual and secretarial occupations, involving sedentary type of work with excessive bending and twisting activities form the major occupational group with LIVDP. Driving is a significant association factor. However, there is no effect of smoking or positive family history. Total 84.5% of the cases have sedentary habits with no sporting activities suggesting the protective role of sports. Emotional factors such as anxiety and stress have a possible role in the etiology of lumbar disc prolapse and its severity of symptoms to require surgery. Disclosure of Interest None declared